Solving the impact of Phthalate plasticizers in relieving environment pollution - Yu Jiajun; Zhang Wei (E3S Web of Conferences)
Climate change had already become one of the most serious problems that human should face. Each year, many problems caused by the plastic called “white pollution”. Some Phthalate (PAEs) substance like DEHP, DEP, and DBP are very common in people’s urine. Those substances can be found in many daily products like food packing and cosmetic. In soil pollution, this plasticizer can be absorbed by plants and ingested by humans, disrupting the body's metabolism and reproductive system and can destroy soil biodiversity and affect the nitrogen cycle in the soil. For air pollution, two aspects the first is that greenhouse vegetables decompose under sunlight and produce some substances such as sulfur dioxide carbon dioxide. The second is the use of building materials containing paints and raw materials that contain this plasticizer finally they will enter in to human body by their breathing system. The accumulation of such plasticizers can cause the accumulation of heavy metals such as zinc and lead. For example, we conducted a joint experiment with Tokyo University last month to test the content of heavy metal ions in Osaka Bay. The food is eaten by the bacteria and will remain in their digestive system. This kind of plastic waste is washed ashore by ocean currents and other geographical factors in the sea, as shown in an experiment on the east coast of New Zealand. By solving these problems, scientists are using two solutions. Frist of all is the scientific way, by using some physical methods like upercritical 95% ethanol is used as the entrainer in fluid extraction (SFE), adding by basing on the concentration of the 0 % to 25 % of the spore powder mass to divide phthalate plasticizers using the metal-organic framework MIL-96(Al) in the simultaneous dispersive microsolid phase extraction of three phthalates and di (2-ethylhexyl) adipate. Moreover, is passing chemical ways like focusing on different concentration of PVC-THF fast remover (PTFR) or DNA walkers. For biological methods, adding Bacterial genera include Comamonas, Sphingomonas, Halomonas, Microbacterium, Mycobacterium, Acinetobacter, Rhodococcus, Pseudomonas, and Bacillus. In future, using different replacement like cashew nutshell liquid (CNSL) CNSL-based plasticizers which is easy and cheap to obtain is a useful way to solve some of these problems. With the efforts of scientists and individuals, in future the danger caused by Phthalate plasticizers can be solved effectively.